An answer to COVID-19: The need to use the maximum capacity of hospitals - Samereh Yaghoubian; Mohammad Ali Jahani; Majid Bahrami; Mohammad Khorshidi; Ghahraman Mahmoudi (فصلنامه ابن سینا, 2020)
Background: COVID-19 crisis posed a major challenge to the hospital management system to which effectiveness, safety, and the patient's centrality can be considered in designing and implementing disease management strategies and controlling the spread of disease in the near future. Lack of data and models for predicting the spread of disease may lead to confusion in health care resources, due to the extent and severity of injuries and disrupt  basic hospital programs and services. Therefore, this study was conducted with the aim of using the maximum capacity of hospitals in the face of COVID-19 pandemic. Materials and methods: The research was conducted through narrative review studies using appropriate keywords such as COVID-19, human resources, finance resources, equipment, and hospitals in reliable electronic databases from March 1 to April 30, 2020, and articles with full text and coherent structure were reviewed. Results: Out of 3,024 identified articles, 62 articles with related title, abstract, and full text were reviewed, and the main findings of the study were classified into two sections: hospital management and activation of hospital wards and staff. Conclusion: Developing emergency programs and activating them in the hospital, explaining the Standard Operating Procedures (SOPs) for the first responders, training how to implement methods of prevention and control of infections in the hospital, organizing human resources, using all available capacities in hospitals, Including human resources, financial resources and equipment, and creating a database will be helpful in dealing with the corona crisis.